The effect of learner-adapted practice schedule and task similarity on motivation and motor learning in older adults. (May 2021) - Beik, Meysam; Fazeli, Davoud
Abstract: The purpose of the present study was to investigate the effect of learner-adapted practice schedule and task similarity on intrinsic motivation and motor learning in older adults. For this purpose, 60 right-handed older adults were randomly divided into six groups of blocked-similar, learner-adapted-similar, random-similar, blocked-dissimilar, learner-adapted-dissimilar, and random-dissimilar. Sequential timing was used as the task, and the intrinsic motivation questionnaire was used for measuring individuals' motivation. The learner-adapted practice was included performing the task in a combination of blocked, serial, and random orders according to error number in each block. The results showed that the learner-adapted practice significantly outperformed than other practice schedules in motivation and motor learning measures in similar and dissimilar conditions. Also, the random schedule resulted in superior performance than the blocked schedule in similar and dissimilar conditions. These findings were discussed according to the challenge point framework. Highlights: This study compared novel versus classic practice schedule in older adults. Learner-adapted practice performed the task between blocked and random practice in acquisition. Learner-adapted practice outperformed the blocked and random practice in retention and transfer. Learner-adapted practice enhance intrinsic motivation compare to blocked and random practice. Learner-adapted practice facilitated optimal challenge during acquisition for older adults.